Siesmic Activity and its Periphery - Lamsal, Min Raj (Himalayan Physics, 2017)
Earthquake is a series of vibrations within the earth's crust. It occurs when the earth's crust break due to geological forces on the rock and adjoining plate. Earthquake refers to a movement or tremor of the earth’s crust that originates naturally and below the surface. An earthquake is a vibration or oscillation of the surface of the earth caused by a transient disturbance of the elastic or gravitational equilibrium of the rocks at or beneath the surface. There are two causes of earthquakes. One is religious concept and the other is modern concept. Earthquakes are of different types according to their place of origin and location. There are so many effects of earthquakes. The Himalayan Physics Vol. 6 & 7, April 2017 (86-91)